Low-frequency and random telegraph noise performance of Ge-based and III-V devices on a Si platform - Claeys, Cor; Agopian, Paula [UNESP]; Alian, Alirezza; Arimura, Hiroaki; Fang, Wen; Martino, Joao; Mitard, Jerome; Neves, Felipe; Oliviera, Alberto; Simoen, Eddy (Institute of Electrical and Electronics Engineers (IEEE), 2017)
This review demonstrates the potential of low frequency noise diagnostics for the characterization of Ge-based and III-V technologies processed on a Si platform. The analysis of traps in both gate dielectrics and semiconductor films is illustrated for state-of-the-art devices.